Hydrolytic enzyme activity in high-rate anaerobic reactors treating municipal wastewater in temperate climates - Paissoni, Eleonora; Jefferson, Bruce; Soares, Ana (Elsevier, 2024)
Particulate matter hydrolysis is the bottleneck in anaerobic treatment of municipal wastewater in temperate climates. Low temperatures theoretically slow enzyme-substrate interactions, hindering utilization kinetics, but this remains poorly understood. β-glucosidase, protease, and lipase activities were evaluated in two pilot-scale upflow anaerobic sludge blanket (UASB) reactors, inoculated with different sludges and later converted to anaerobic membrane bioreactors (AnMBRs). Despite similar methane production and solids hydrolysis rates, significant differences emerged. Specific activity peaked at 37 °C, excluding the predominance of psychrophilic enzymes. Nevertheless, the Michaelis-Menten constant (Km) indicated high enzyme-substrate affinity at the operational temperature of 15–20 °C, notably greater in AnMBRs. It is shown, for the first time, that different seed sludges can equally adapt, as hydrolytic enzymatic affinity to the substrate reached similar values in the two reactors at the operational temperature and identified that membrane ultrafiltration impacted hydrolysis by a favourable enzyme Michaelis-Menten constant.
Keywords: Anaerobic membrane bioreactor; Glucosidase; Lipase; Low temperature; Protease; UASB reactor